(untitled) (American Journal of Technology and Applied Sciences, 2023)
This paper presents the results of experimental studies of the effect of anomalous photo voltage. Ways to study the properties of anomalous photo voltage (APV) elements have been formulated and determined. The results of experimental studies to determine the micro parameters of APN films are presented.